A novel variant in TAF1 affects gene expression and is associated with X-linked TAF1 intellectual disability syndrome. Issue 3 (16th July 2018) - Hurst, Sarah E.; Liktor-Busa, Erika; Moutal, Aubin; Parker, Sara; Rice, Sydney; Szelinger, Szabolcs; Senner, Grant; Hammer, Michael F.; Johnstone, Laurel; Ramsey, Keri; Narayanan, Vinodh; Perez-Miller, Samantha; et al.
Abstract : We investigated the genome of a 5-year-old male who presented with global developmental delay (motor, cognitive, and speech), hypotonia, possibly ataxia, and cerebellar hypoplasia of unknown origin. Whole genome sequencing (WGS) and mRNA sequencing (RNA-seq) were performed on a family having an affected proband, his unaffected parents, and maternal grandfather. To explore the molecular and functional consequences of the variant, we performed cell proliferation assays, quantitative real-time PCR (qRT-PCR) array, immunoblotting, calcium imaging, and neurite outgrowth experiments in SH-SY5Y neuroblastoma cells to compare the properties of the wild-type TATA-box-binding protein factor 1 ( TAF1 ), deletion of TAF1, and TAF1 variant p.Ser1600Gly samples. The whole genome data identified several gene variants. However, the genome sequence data failed to implicate a candidate gene as many of the variants were of unknown significance. By combining genome sequence data with transcriptomic data, a probable candidate variant, p.Ser1600Gly, emerged in TAF1 . Moreover, the RNA-seq data revealed a 90:10 extremely skewed X-chromosome inactivation (XCI) in the mother. Our results showed that neuronal ion channel genes were differentially expressed between TAF1 deletion and TAF1 variant p.Ser1600Gly cells, when compared with their respective controls, and that the TAF1 variant may impair neuronal differentiation and cell proliferation. Taken together, our data suggest that this novel variant in TAF1 plays a key role in the development of a recently described X-linked syndrome, TAF1 intellectual disability syndrome, and further extends our knowledge of a potential link between TAF1 deficiency and defects in neuronal cell function.